Pengaruh Pemberian Edukasi Berbasis Digital Cardicraf terhadap Tingkat Kepatuhan Monitoring Self-Care Management Pasien Gagal Jantung - Dewi Rahmawati; Fina Catur Hardiyanti; Siti Iyah Fauziyah; Indah Mae Nur Falakh; Trisna Nurhidayat; Triyandi Algifari (Faletehan Health Journal, 2022)
Recently, the prevalence of morbidity and mortality of heart failure cases was increasing, leading to complex medications and treatments, as well as the incidence of rehospitalization. In addition, the complications that occur had an impact on the patient's quality of life decreases. One of the efforts to prevent the worsening conditions was through self-care management which can be improved through digital-based education. The purpose of this study was to determine the effects of education through digital media applications Cardicraf on self-care management compliance of heart failure (HF) patients. The research design used quasy experiment with one group pre and post-test without control group. The study samples were 25 respondents based on inclusion criteria with purposive sampling techniques. The research instrument were Morisky 8-item Medication Adherence Questionnaire and Self-Care of Heart Failure Index (SCHFI). The analysis data used paired sample t-test. The results showed the average self-care management compliance before intervention with Cardicraf was 59.92 and after was 85.75. The results of the statistical test obtained p value 0.000 which was concluded that there was the effects of education with Cardicraf on self-care management compliance of HF patients. This application needed improvements to be used on platforms playstore; thus, it can be used broaderly and easily by society and help health workers to do assessments and monitoring to heart failure patients.